Strategi Komunikasi OJK Regional 9 Kalimantan dalam Mengedukasi Literasi dan Inklusi Keuangan Kepada Masyarakat - Amelia Puspita; Devia Hetty Hernany; Riska Aulia Noor (Journal on Education, 2024)
In the era of the industrial revolution 4.0 5.0, it is interpreted as leading to high competition in various sectors that are in direct contact with society's needs. Because at this time society is required to live side by side with technology, master and utilize technology. However, the fact is that the level of digital literacy in Indonesia is still very low. Looking at the aspect of communication activities, the ease of obtaining information, digital transactions, digital capital, etc. can be accessed easily and quickly without having to do activities outside the home. Not only that, there are also negative impacts on society such as digital technology services. Therefore, implementing an integrated regulatory and supervisory system for all activities in the financial services sector that is clearly regulated is the main concern of the Financial Services Authority (OJK). Based on the explanation presented, the author is interested in conducting research on "Communication Strategy of the Regional 9 Kalimantan Financial Services Authority (OJK) in Educating Financial Literacy and Inclusion to the Community." The research, which will be carried out over a period of eight months, is aimed at finding out the Kalimantan Regional 9 Financial Services Authority (OJK) Communication Strategy in Educating and Financial Inclusion to the Community. The research method used is a qualitative method. Design data collection techniques using interview and documentation techniques. Then design data analysis using qualitative analysis techniques. (;).